Dielectric Relaxation Study of Diethylene Glycol Monomethyl Ether with Aromatic Compounds Using Time Domain Reflectometry Technique - Maheshmalkar, P.R.; Sayyad, S.B.; Shivalkar, K.N.; Kamble, S.P.; Undre, P.B.; Khirade, P.W. (Asian Journal of Chemistry, 2012)
Complex permittivity spectra e* = e'-je" of binary mixtures of diethylene glycol monomethyl ether with aromatic compounds were obtained in the frequency range of 10 MHz to 20 GHz at different temperatures 288, 298, 308 and 318 K using the time domain reflectometry technique. Dielectric parameters viz. dielectric constant (e0), relaxation time (t) were obtained from complex permittivity spectra using nonlinear least squares fit method using these parameters excess permittivity (e0E), excess inverse relaxation time (1/t)E, Bruggeman factor (fB), Kirkwood correlation factor (geff) were determined. On the basis of above parameters, intermolecular interaction and dynamics of molecules at molecular level are predicated.